2019
DOI: 10.1016/j.jaci.2019.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Selective role of neurokinin B in IL-31–induced itch response in mice

Abstract: US children is in line with data from the single-center population-based birth cohorts from Israel and Spain, reporting cumulative incidence of 0.34% and 0.7%, respectively. 4,5 Our study provides the first-ever estimate of FPIES prevalence in adults. To date, only several small case series of adult patients were published. 2 Our report has several limitations. The survey was not developed to estimate FPIES prevalence, and details of the trigger foods and symptoms are lacking. Although the survey asked about p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
0
20
2
Order By: Relevance
“…Many pruritogenic axes such as chloroquine/MrgprA3- or histamine/H1R-induced pruritus require natriuretic polypeptide b (Nppb) and gastrin-releasing peptide (GRP) and their respective receptors, natriuretic peptide receptor A (NPRA) and GRP receptor (GRPR), to transmit the sensation of itch in the spinal cord [ 55 , 56 ] ( Figure 2 ). However, IL-31-induced pruritus requires neurokinin B (NKB) instead of Nppb [ 56 ]. NKB binds neurokinin receptor 3 (NK3R) and induces the release of GRP, which mediates the sensation of pruritus [ 56 ] ( Figure 2 ).…”
Section: Il-31 and Pruritusmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pruritogenic axes such as chloroquine/MrgprA3- or histamine/H1R-induced pruritus require natriuretic polypeptide b (Nppb) and gastrin-releasing peptide (GRP) and their respective receptors, natriuretic peptide receptor A (NPRA) and GRP receptor (GRPR), to transmit the sensation of itch in the spinal cord [ 55 , 56 ] ( Figure 2 ). However, IL-31-induced pruritus requires neurokinin B (NKB) instead of Nppb [ 56 ]. NKB binds neurokinin receptor 3 (NK3R) and induces the release of GRP, which mediates the sensation of pruritus [ 56 ] ( Figure 2 ).…”
Section: Il-31 and Pruritusmentioning
confidence: 99%
“…However, IL-31-induced pruritus requires neurokinin B (NKB) instead of Nppb [ 56 ]. NKB binds neurokinin receptor 3 (NK3R) and induces the release of GRP, which mediates the sensation of pruritus [ 56 ] ( Figure 2 ).…”
Section: Il-31 and Pruritusmentioning
confidence: 99%
“…The transcription factor hypoxia-inducible factor-2α (HIF-2α), also called endothelial Per-Arnt-Sim (PAS) domain protein 1 (EPAS1), is required for the production of IL-31 [60]. Binding of IL-31 to IL-31-sensitive dorsal root ganglion cells induces the production of neurokinin B and activates its neurokinin 3 receptor, which then triggers the production of an itch mediator, gastrin-releasing peptide [63]. A recent study also revealed a significant role of P2X3 receptor-positive nerves in chronic pruritus [64].…”
Section: Role Of Il-31 and Il-13/il-4 In Atopic Pruritusmentioning
confidence: 99%
“…Moreover, the itch responses to subcutaneously injected IL‐31 were significantly attenuated in Nppb ‐KO mice and mice treated with Nppb‐saporin, a toxin that ablated 70% BNP receptor positive neurons in the spinal cord (Mishra & Hoon, ; Pitake et al, ). On the contrary, itch induced by intradermal injection of IL‐31 in mice was not affected by intrathecal injection of Nppb‐saporin and neurokinin B was selectively involved in IL‐31‐induced itch (Sakata et al, ). However, the percentage of the neuronal population ablated is lacking in this later study.…”
Section: Differential Expression Of Bnp and Its Receptors In Periphermentioning
confidence: 99%